Women employment in agricultural sector: Effects on livelihoods: Livelihood of agricultural women (Journal of the Bangladesh Agricultural University, 2019)
Women in Bangladesh are involved with agriculture in planting, harvesting and post-harvest processing. Present study investigated the socio-economic, hygienic and maternal health of the women working in agricultural sector (employee) and women who are involved in other works (non-employee) in the same community to evaluate impacts of agriculture on women life style. Data was collected from Chittagong, Dinajpur and Mymensingh district using questionnaire survey. The survey results revealed that medium household size (61.9% and 57.8%), primary education (51.4% and 49.1%), married (93.6% and 91.4%) was dominant among employee and non-employee women, respectively. Average monthly household income and expenditure of the employees were Tk. 11532 and Tk. 8926, respectively while in non-employee women were Tk. 9686 and Tk. 7848, respectively. Most of the employee and non-employee women had facilities for drinking tube-well water (91.9% and 81.5%) and use polli electricity (69.9% and 68.2%) in the areas. This indicates that higher income from agriculture has a positive impact on life style of employee women. Clean house, hand washing, garbage disposal and ingredients wash before cooking constituted highest percentage of the respondents in both cases. Current study revealed that health check during pregnancy, T.T. coverage and normal delivery process was good among the employee women. Body Mass Index (BMI) results revealed that 68.2% employee women was under normal weight while 42.8% non-employee women was underweight. Besides, obesity rate was significantly higher among the non-employee women (25.4%) which is only 2.9% among the employee community. The study observed and suggesting that employee women in agriculture have better life style, more income, hygiene practice, good maternal health and better nutritional status than the non-employee women in the same community.J Bangladesh Agril Univ 17(3): 375–379, 2019